2022
DOI: 10.1002/ece3.9305
|View full text |Cite
|
Sign up to set email alerts
|

Niche and range dynamics of Tasmanian blue gum (Eucalyptus globulus Labill.), a globally cultivated invasive tree

Abstract: The ecological niche concept has provided insights into various areas in ecology and biogeography. Although there remains much controversy regarding whether species niches are conserved across space and time, many recent studies have suggested that invasive species conserve their climatic niche between native and introduced ranges; however, whether the climatic niche of cultivated invasive species, whose niches are strongly affected by human activities, are conserved between native and introduced ranges remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…In the present study, however, we found that the climatic niche breadth of GSs in North America was 1.38 times the breadth of those in Europe, and the climatic potential range of GSs in North America was 2.45 times that of the climatic potential range of GSs in Europe. This suggests that small climatic niche shifts may induce considerable range shifts, which is supported by several recent studies 76,81,82 . Although both the climatic potential range shifts and niche shifts of invasive species can be used to evaluate their invasion risk from a climate suitability perspective, niche shifts may be more sensitive than range shifts, and invasive species showing greater niche shifts may warrant more attention in biological conservation and invasion biology.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study, however, we found that the climatic niche breadth of GSs in North America was 1.38 times the breadth of those in Europe, and the climatic potential range of GSs in North America was 2.45 times that of the climatic potential range of GSs in Europe. This suggests that small climatic niche shifts may induce considerable range shifts, which is supported by several recent studies 76,81,82 . Although both the climatic potential range shifts and niche shifts of invasive species can be used to evaluate their invasion risk from a climate suitability perspective, niche shifts may be more sensitive than range shifts, and invasive species showing greater niche shifts may warrant more attention in biological conservation and invasion biology.…”
Section: Discussionmentioning
confidence: 64%
“…This suggests that small climatic niche shifts may induce considerable range shifts, which is supported by several recent studies. 76,81,82 Although both the climatic potential range shifts and niche shifts of invasive species can be used to evaluate their invasion risk from a climate suitability perspective, niche shifts may be more sensitive than range shifts, and invasive species showing greater niche shifts may warrant more attention in biological conservation and invasion biology.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus relative to their niche breadth ratios, i.e., 1.549 vs. 1.018 and 3.824 vs. 1.391, respectively. This might indicate that small niche shifts in them could induce their large range shifts and that niche shifts might be a more important indicator for biological invasion assessments [74].…”
Section: Discussionmentioning
confidence: 99%
“…A weight proportional to their TSS evaluation was given to each model's projection [71]. As required by presence-only SDMs, we conducted a three-time random selection at a global terrestrial scale (except Antarctica) as follows: equal numbers of pseudo absences when the number of real occurrence records was over 1000, or 1000 pseudo absences randomly were selected, following Cao et al [74]. We used the maximization sensitivity-specificity sum thresholds to calibrate the potential ranges of the two Aedes species, as suggested by Liu et al (2016) [75].…”
Section: Potential Ranges Of the Two Aedes Speciesmentioning
confidence: 99%
“…Investigating the range dynamics of alien invasive species (AIS) and the underlying mechanisms is of great significance since efficient strategies against biological invasions can be developed [15][16][17][18]. Therefore, an essential need is to project the range dynamics of AIS under future climate change scenarios [19][20][21]. Previous studies have shown that the ranges of AIS may be modified by future climate change, probably because AIS will track their once-occupied climatic-suitable habitats, and climate change could reallocate suitable habitats [12,22,23].…”
Section: Introductionmentioning
confidence: 99%